2015
DOI: 10.1007/s10337-015-2946-3
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Enantiomeric Purity of Trelagliptin by Pre-Column Derivatization and Liquid Chromatography on a Chiral Stationary Phase

Abstract: validated by analysis of bulk samples of trelagliptin of different enantiomeric purity. It was demonstrated that the method was accurate, robust, and sensitive, and enabled practical analysis of real samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…It is important for the explicit isolation of β-blocker enantiomers that are underivatized. It can also be used to separate aryl propionic acid NSAID enantiomers as well as other drugs (Yang et al, 2008).…”
Section: Pirkle 1-jmentioning
confidence: 99%
“…It is important for the explicit isolation of β-blocker enantiomers that are underivatized. It can also be used to separate aryl propionic acid NSAID enantiomers as well as other drugs (Yang et al, 2008).…”
Section: Pirkle 1-jmentioning
confidence: 99%
“…Indirect chromatographic resolution utilizes a chiral derivatizing agent for enantioseparation which is based on the formation of covalent diastereomers. 83 This addition step decreases the importance of indirect resolution compared to direct resolution. Some other disadvantages include high purity, stability, sensitivity, selectivity, and proper selection of reagents as well as the possibility of racemization during the reaction.…”
Section: Racemic Drug Resolution (Covalent or Transient Diastereomer ...mentioning
confidence: 99%
“…TLN analysis and bioanalysis literature review showed many methods [7][8][9][10][11][12][13] for TLN assay either in dosage form or as biological fluids (pharmacokinetic parameters). An LC method for determination of enantiomeric purity of TLN was reported [7].…”
Section: Introductionmentioning
confidence: 99%
“…TLN analysis and bioanalysis literature review showed many methods [7][8][9][10][11][12][13] for TLN assay either in dosage form or as biological fluids (pharmacokinetic parameters). An LC method for determination of enantiomeric purity of TLN was reported [7]. Some other stability-indicating LC methods were developed for TLN assay in the presence of impurities and/or degradation products [8][9][10][11], but all those methods were not related to biological assay of TLN.…”
Section: Introductionmentioning
confidence: 99%